Li‐ and Mn‐Rich Cathode Materials: Challenges to Commercialization - Zheng, Jianming; Myeong, Seungjun; Cho, Woongrae; Yan, Pengfei; Xiao, Jie; Wang, Chongmin; Cho, Jaephil; Zhang, Ji‐Guang (Advanced energy materials, 2017)
The lithium‐ and manganese‐rich (LMR) layered structure cathodes exhibit one of the highest specific energies (≈900 W h kg−1) among all the cathode materials. However, the practical applications of LMR cathodes are still hindered by several significant challenges, including voltage fade, large initial capacity loss, poor rate capability and limited cycle life. Herein, we review the recent progress and in depth understandings on the application of LMR cathode materials from a practical point of view. Several key parameters of LMR cathodes that affect the LMR/graphite full‐cell operation are systematically analyzed. These factors include the first‐cycle capacity loss, voltage fade, powder tap density, and electrode density. New approaches to minimize the detrimental effects of these factors are highlighted in this work. We also provide perspectives for the future research on LMR cathode materials, focusing on addressing the fundamental problems of LMR cathodes while keeping practical considerations in mind. An overview of current research activities addressing the key challenges of LMR cathodes is presented, focusing on discussion of the facile strategies to improve the initial Coulombic efficiency, working voltage stability, and rate capability. Promising perspectives for LMR studies are suggested by providing full‐cell data of LMR electrodes with commercialization specifications.